Genome-based surveillance reveals cross-transmission of MRSA ST59 between humans and retail livestock products in Hanzhong, China - Zhang, Wei; Wang, Xueshuo; Zhao, Linna; Gu, Yihai; Chen, Yiwen; Liu, Na; An, Lin; Bai, Li; Chen, Yanjiong; Cui, Shenghui (Frontiers in Microbiology, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) has been recognized in hospitals, community and livestock animals and the epidemiology of MRSA is undergoing a major evolution among humans and animals in the last decade. This study investigated the prevalence of MRSA isolates from ground pork, retail whole chicken, and patient samples in Hanzhong, China. The further characterization was performed by antimicrobial susceptibility testing and in-depth genome-based analysis to identify the resistant determinants and their phylogenetic relationship. A total of 93 MRSA isolates were recovered from patients (n = 67) and retail livestock products (n = 26) in Hanzhong, China. 83.9% (78/93) MRSA isolates showed multiple drug resistant phenotype. Three dominant livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) sequence types were identified: ST59-t437 (n = 47), ST9-t899 (n = 10) and ST398 (n = 7). There was a wide variation among sequence types in the distribution of tetracycline-resistance, scn-negative livestock markers and virulence genes. A previous major human MRSA ST59 became the predominant interspecies MRSA sequence type among humans and retail livestock products. A few LA-MRSA isolates from patients and livestock products showed close genetic similarity. The spreading of MRSA ST59 among livestock products deserving special attention and active surveillance should be enacted for the further epidemic spread of MRSA ST59 in China. Data generated from this study will contribute to formulation of new strategies for combating spread of MRSA.